Ljubezen na prvi klik - Kuhar, Roman (Družboslovne razprave, 2010)
The ever wider accessibility of the Internet as a medium and space for individual and group action in different life contexts has also enabled its broader use in individuals' most intimate life contexts. Globally as well as in Slovenia the Internet has become an attractive way of looking for new friends and/or partners. In the paper some basic characteristics of Internet dating in Slovenia are discussed. User experiences of Internet dating web portals for meeting partners in virtual space are presented, along with the user profile characteristics they pay attention to and ways of self-representation in virtual space. The transition from virtual to real space (first face-to-face contact, first sexual contact) is also considered. These dimensions of Internet dating are interpreted with regard to two key factors: gender and sexual orientation. Data were collected in the first systematic survey of Internet dating in Slovenia in 2007 on a non-random sample of 1,334 users of the biggest Slovenian Internet dating web portals.
Keywords: Internet; Web portals; Spletni portali; Sexuality; Intimacy (Psychology); sexual intercourse; Spolnost; Intimnost; Partnership; Partnerstvo; Slovenia; Slovenija; medosebno komuniciranje; spletni zmenki